A Comparison of Patient-Reported Outcome Measures of Quality of Life By Dialysis Modality in the Treatment of Kidney Failure: A Systematic Review. (October 2020) - Budhram, Brandon; Sinclair, Alison; Komenda, Paul; Severn, Melissa; Sood, Manish M.
Background: There is an increasing demand to incorporate patient-reported outcome measures (PROMs) such as quality of life (QOL) in decision-making when selecting a chronic dialysis modality. Objective: To compare the change in QOL over time among similar patients on different dialysis modalities to provide unique and novel insights on the impact of dialysis modality on PROMs. Design: Systematic reviews, randomized controlled trials, and nonrandomized controlled trials were examined via a comprehensive search strategy incorporating multiple bibliographic databases. Setting: Data were extracted from relevant studies from January 1, 2000 to December 31, 2019 without limitations on country of study conduction. Patients: Eligible studies included adults (≥18 years) with end-stage kidney disease of any cause who were prescribed dialysis treatment (either as lifetime treatment or bridge to transplant). Measurements: The 5 comparisons were peritoneal dialysis (PD) vs in-center hemodialysis (ICHD), home hemodialysis (HHD) vs ICHD, HHD modalities compared with one another, HHD vs PD, and self-care ICHD vs traditional nurse-based ICHD. Methods: Included studies compared adults on different dialysis modalities with repeat measures within individuals to determine changes in QOL between dialysis modalities (in-center or home dialysis). Methodological quality was assessed by the Scottish Intercollegiate Guidelines Network (SIGN 50) checklist. A narrative synthesis was conducted, synthesizing the direction and size of any observed effects across studies. Results: Two randomized controlled trials and 9 prospective cohort studies involving a combined total of 3711 participants were included. Comparing PD and ICHD, 5 out of 9 studies found significant differences ( P < .05) favoring PD in the change of multiple QOL domains, including "physical component score, " "role of social component score, " "cognitive status, " "role limitation due to emotional function, " "role limitation due to physical function, " "bodily pain, " "burden of kidney disease, " "effects of kidney disease on daily life, " "symptoms/problems, " "sexual function, " "finance, " and "patient satisfaction." Conversely, 3 of these studies demonstrated statistically significant differences ( P < .05) favoring ICHD in the domains of "role limitation due to physical function, " "general health, " "support from staff, " "sleep quality, " "social support, " "health status, " "social interaction, " "body image, " and "overall health." Comparing HHD and ICHD, significant differences ( P < .05) favoring HHD for the QOL domains of "general health, " "burden of kidney disease, " and the visual analogue scale were reported. Limitations: Our study is constrained by the small sample sizes of included studies, as well as heterogeneity among both study populations and validated QOL scales, limiting inter-study comparison. Conclusions: We identified differences in specific QOL domains between dialysis modalities that may aid in patient decision-making based on individual priorities. Trial registration: PROSPERO Registration Number: CRD42016046980. Primary funding source: The original research for this study was derived from the Canadian Agency for Drugs and Technologies in Health (CADTH) 2017 optimal use report, titled "Dialysis Modalities for the Treatment of End-Stage Kidney Disease: A Health Technology Assessment." The CADTH receives funding from Canada's federal, provincial, and territorial governments, with the exception of Quebec.